Clinical study of hernia in females - Kappikeri, Vijaykumar S.; Thalasta, Puneeth (International Surgery Journal, 2017)
Background: Abdominal wall hernia is the most commonly encountered clinical problem in the surgical setting and also the incidence of various types of hernias are known to have gender variations. This study was done to analyse the pattern of different types of hernia and their incidence in female patients. Methods: This was a retrospective study done at Basaveshwara Teaching and General Hospital, Kalaburagi, Karnataka, India from January 2012 to December 2014. All the female patients who presented with different types of hernia like inguinal, umbilical, ventral, congenital and diaphragmatic hernias irrespective of the age have been included in the study from January 2012 to December 2014. Results: In this study total of 87 cases of different types of hernias were studied including ventral, inguinal, umbilical and diaphragmatic hernias. Among which ventral hernias were the most common including 42 cases and among them one case presented as obstructed hernia and the most common age of incidence was 31-40 years. The next most common presentation was inguinal hernia with total of 29 cases and the paediatric age group (0-10 years) was the most common presentation. The next common hernia was umbilical hernia and the most common age of presentation was 21-40 years. The least common presentation was that of diaphragmatic hernia with only 4 cases, age of the patients being 60 and above. Conclusions: In present study, most commonly encountered hernia was ventral hernia followed by inguinal, then umbilical and lastly diaphragmatic hernias.